Enkele teorie, aspekte van Theodore soos verwoord in sy tuum" - Dreyer, W. A. (Hervormde teologiese studies, 1996)
Some aspects of Theodore Beza's political theory in his 'Deiure magistratuum' Beza's 'De iure magistratuum' had, directly or indirectly, a great influence on the development of political theory in Western Europe. In this paper the historical background of the 'De magistratuum' is discussed, as well as basic political concepts which form the basis of Beza's political theory, such as the origin of government and law, political contract and covenant, political pluralism, the right to resist government, justice, democracy, the priority of the people over government and rule of law.